Mortgage System and Asymmetric Information - Jasinskaitė, Salomėja (Ekonomika, 1997)
The article deals with one of the main default risk factors, asymmetric information prevailing in the credit markets. In the first part of the article reasons for the great level of asymmetric information in the credit markets of countries of transition that makes credit rationing stronger are analysed. In the second part of the article suggestions for decreasing the asymmetric information factor with the help of institutional innovations are presented. The main point of the suggestions is the founding of a mortgage institution and the establishment of a mortgage register which would provide creditors with reliable information concerning the mortgages they have been charged.